Environmental performance assessment of Napier grass for bioenergy production. (1st November 2017) - Nimmanterdwong, Prathana; Chalermsinsuwan, Benjapon; Østergård, Hanne; Piumsomboon, Pornpote
Abstract: The industrial production of chemicals and energy carriers has grown enormously with the support of new technologies. A proper assessment is needed to provide broader aspects for long-term sustainability. The purpose of this study was to evaluate the environmental sustainability of a biorefinery based on lignocellulosic biomass feedstock using emergy analysis and to propose the method to minimize material consumption and waste. The concept of emergy is to express the record of all resources used by the biosphere in earlier steps to produce a product or service, in term of solar energy equivalence. This idea provides the quantitative indicators involving the resource use and the percent renewability of the systems. For the proposed biorefinery model, Napier grass ( Pennisetum purpureum ) grown in Thailand was used as lignocellulosic feedstock. An emergy assessment was performed in two parts, comprised of the evaluation of the feedstock cultivation and of a biorefinery producing liquid fuels, methanol, steam, electricity and other by products, i.e., high purity CO2, sulfur. The emergy results revealed that the bio-based products depend mostly on non-renewable resources used in both biomass cultivation and biorefinery stages. For Napier grass cultivation, most of the emergy support came from local resources in term of evapotranspiration of Napier grass (33%) and the diesel consumption during the cultivation process (21%). The emergy sustainability indicator of the cultivation was 0.81. The emergy sustainability indicator of the whole process from cultivation to biorefinery stages dropped to 0.25, since the biorefinery section required solely economic inputs of which most were non-renewable. In conclusion, the implementation of the integrated biorefinery concept could minimize material consumption and waste generation and it also has higher performance in terms of the emergy compared to other existing processes. Highlights: Emergy analysis is employed to biomass cultivation and biorefinery processes. Heavy consumption of non-renewable resources in Napier grass cultivation was found. The proposed biorefinery can achieve a higher emergy performance than existing ones. The proposed biorefinery consists of material and energy through reuse and recycling. Human labor and renewable resource accounting was discussed.